The impact of localising sustainable development goals (SDG) in selected Sabah parliamentary constituencies through service-learning concept - Muhamad Azwan Abd Rahman; Eko Prayitno Joko; Muhammad Rahimi Hasan; Nik Hasif (Penerbit UTHM, 2023)
This article presents the impact evaluation of the Solution Providers Project, a flagship program of The All-Party Parliamentary Group Malaysia – Sustainable Development Goals (APPGM-SDG) on Civil Society Organization (CSO) Alliance, aimed at reducing inequalities in selected constituencies in Sabah, Malaysia. Focusing on Sustainable Development Goals (SDGs) through the lens of impact evaluator, this study adopts a service-learning conceptual framework and a mix-method research design, combining qualitative approaches (evaluator observation, focus group discussions) with numerical assessments on 15 selected constituencies. Findings reveal that while solution providers express over-optimism about reported projects, beneficiaries encounter diverse challenges in experiencing the intended impact. Data from focus group discussions highlights both success stories and obstacles, showcasing skill acquisition through hands-on experiences. However, beneficiaries’ understanding on SDGs is still at a mediocre level, despite emphasis during planning and execution. Overall, the findings from this impact evaluation can be instrumental in informing decision-making, improving program design, and shedding light on specific policy areas, particularly in reducing multidimensional inequality such as income, consumption inequality and the quality of digital education in the Sabah region.